Políticas de financiamento às micro e pequenas empresas no estado de Minas Gerais:uma análise do período recente - Cardoso, Flávio Guimarães (2003)
The aim of this paper is to present the main financing policies to Micro Companies (ME) and Small Companies (EPP) 1 offered within the state of Minas Gerais, in order to identify the central problems that these companies encounter in accessing credit and the effective results of these policies for this segment of companies. In this sense, the objective is to evaluate the specific credit programs for micro and small companies (MSEs) offered mainly by government banks, which traditionally are the largest providers of resources to the sector. For this study, special emphasis is given to the role of BDMG (Development Bank of Minas Gerais) 2, where the scope of its operations, the available credit lines and the processes for requesting resources and their requirements are analyzed. The main hypothesis that guides this work is that, despite the existence of several lines of credit aimed at the segment of micro and small companies, the types of contracts, requirements, terms and fees charged in the market are at odds with the needs and their possibilities. The interest rates are, in large part, high for the reality of the sector and few financial institutions offer lines with interest rates that are "cheaper" than those currently practiced in the market, which seriously compromises the payment capacity of the companies that capture these resources. Even in government institutions, the release of credit is complex, as they do not want to take risks and thus seek to cover themselves with real guarantees, which in most cases can reach more than 200% of the requested financing amount. There are several policy actions to support small businesses, such as: professional training (training), differentiated tax regimes, active job creation policies and credit support policies. MSEs have their strategic importance in order to reduce the unemployment rate that is growing in the country and in the world. It is observed that, both in developed and underdeveloped countries, since the 1980s, the segment has been growing and becoming increasingly representative in economies, thus it is noted that MSEs not only in Brazil, but in a large part of the countries of the globe, are responsible for a significant portion of the generation of jobs and income in these economies.